2023
DOI: 10.3389/fpubh.2023.1136939
|View full text |Cite|
|
Sign up to set email alerts
|

Bibliometric and visual analysis of machine learning-based research in acute kidney injury worldwide

Abstract: BackgroundAcute kidney injury (AKI) is a serious clinical complication associated with adverse short-term and long-term outcomes. In recent years, with the rapid popularization of electronic health records and artificial intelligence machine learning technology, the detection rate and treatment of AKI have been greatly improved. At present, there are many studies in this field, and a large number of articles have been published, but we do not know much about the quality of research production in this field, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The most commonly used algorithms are gradient boosting algorithms and support vector machine algorithms, especially the XGBoost algorithm, which stands out in multiple studies. A recent bibliometric study also showed that the term ‘XGBoost’ holds a dominant position in recent machine learning-based AKI research [ 64 ]. In addition to reflecting the nonlinear relationships between variables, the unique advantage of the XGBoost algorithm lies in its ability to automatically handle missing values and control the overfitting of the model while processing large-scale datasets [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used algorithms are gradient boosting algorithms and support vector machine algorithms, especially the XGBoost algorithm, which stands out in multiple studies. A recent bibliometric study also showed that the term ‘XGBoost’ holds a dominant position in recent machine learning-based AKI research [ 64 ]. In addition to reflecting the nonlinear relationships between variables, the unique advantage of the XGBoost algorithm lies in its ability to automatically handle missing values and control the overfitting of the model while processing large-scale datasets [ 65 ].…”
Section: Discussionmentioning
confidence: 99%